1995
DOI: 10.1002/hep.1840210505
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and portal vein thrombosis in cirrhosis: Possible role in development of parenchymal extinction and portal hypertension

Abstract: Obliterative lesions in portal veins (PVs) and hepatic veins (HVs) of all sizes are known to occur in cirrhotic livers. PV lesions have generally been attributed to thrombosis, but the pathogenesis of the HV (veno-occlusive) lesions is unknown. We have studied 61 cirrhotic livers removed at transplantation to clarify the prevalence, distribution, and pathogenesis of venous lesions, as well as the association of these lesions with other morphological features and clinical morbidity. Intimal fibrosis that is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
319
0
10

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(339 citation statements)
references
References 24 publications
10
319
0
10
Order By: Relevance
“…The 2 patients in our series who presented with infarct had an extremely rapid downward course (subfulminant hepatic failure). It has been proposed that occlusion of the intrahepatic portal veins leads to the development of parenchymal extinction in cirrhosis 14 ; infarcts observed in BCS may represent the acute form of parenchymal extinction.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 patients in our series who presented with infarct had an extremely rapid downward course (subfulminant hepatic failure). It has been proposed that occlusion of the intrahepatic portal veins leads to the development of parenchymal extinction in cirrhosis 14 ; infarcts observed in BCS may represent the acute form of parenchymal extinction.…”
Section: Discussionmentioning
confidence: 99%
“…This ischemic shrinking and infarction of acini has been termed ''focal parenchymal extinction.'' 100 When a large number of extinction lesions are present, the anatomic features of cirrhosis are invariably present. Cases of congestive cirrhosis, autoimmune hepatitis, viral hepatitis, and cholestatic hepatitides such as primary biliary cirrhosis and primary sclerosing cholangitis all provide histological evidence for the development of cirrhosis secondary to hepatic and portal vein phlebitis.…”
Section: The Role Of Vascular Thrombosis In the Pathogenesis Of Portalmentioning
confidence: 99%
“…The intrahepatic microthrombi are thought to play a role in the progression of fibrosis and to result in local ischemia. 19 Patients with FV Leiden have been shown to have a faster progression of hepatitis. 20 Tripodi et al have shown that the hypercoagulability of plasma from patients with cirrhosis appears to result from increased levels of FVIII and decreased levels of protein C. 21 Thrombomodulin does not down-regulate thrombin generation in plasma from chronic liver disease patients as effectively as it does in plasma from healthy subjects, contributing to the risk of thrombosis in liver disease 11,22 …”
Section: Thrombosis Risk In Patients With Liver Diseasementioning
confidence: 99%